Imaging-based chemical screens using normal and glioma-derived neural stem cells. (26th July 2010) - Danovi, Davide; Falk, Anna; Humphreys, Peter; Vickers, Richard; Tinsley, Jon; Smith, Austin G.; Pollard, Steven M.
Abstract : The development of optimal culture methods for embryonic, tissue and cancer stem cells is a critical foundation for their application in drug screening. We previously described defined adherent culture conditions that enable expansion of human radial glia-like fetal NS (neural stem) cells as stable cell lines. Similar protocols proved effective in the establishment of tumour-initiating stem cell lines from the human brain tumour glioblastoma multiforme, which we termed GNS (glioma NS) cells. Others have also recently derived more primitive human NS cell lines with greater neuronal subtype differentiation potential than NS cells, which have similarities to the early neuroepithelium, named NES (neuroepithelial stem) cells. In the present paper, we discuss the utility of these cells for chemical screening, and describe methods for a simple high-content live-image-based platform. We report the effects of a panel of 160 kinase inhibitors (Inhibitor Select I and II; Calbiochem) on NES cells, identifying three inhibitors of ROCK (Rho-associated kinase) as promoting the expansion of NES cell cultures. For the GNS cells, we screened a panel of 1000 compounds and confirmed our previous finding of a cytotoxic effect of modulators of neurotransmitter signalling pathways. These studies provide a framework for future higher-throughput screens.